Skrining Motorik dan Sensorik untuk Meningkatkan Deteksi Dini Perkembangan Anak Usia Dini di TK Bakti Insani" - Meilirianta Meilirianta; Theophylia Melisa Manumara (Jurnal Medika: Medika, 2026)
Developmental delays in early childhood often go undetected due to limited understanding and skills in conducting early identification, particularly in motor and sensory aspects. This community service program aimed to enhance early detection abilities for young children’s development through motor and sensory screening at TK Bakti Insani. The activities included providing outreach to teachers and parents on the importance of early detection, training on the use of simple screening instruments, and assessing children’s development based on gross motor, fine motor, and sensory indicators. The results showed that the screening successfully identified several children who required additional stimulation or professional referral. Moreover, teachers’ knowledge of developmental stages and appropriate stimulation improved significantly. This program highlights that motor and sensory screening is a strategic step to strengthen early detection efforts and improve the quality of early childhood education services at TK Bakti Insani.